2024
DOI: 10.1108/jima-02-2023-0036
|View full text |Cite
|
Sign up to set email alerts
|

Consumer shift behavior from conventional to Islamic banking: decision-making analysis through AHP

Muneer Ahmad,
Muhammad Bilal Zafar,
Abida Perveen

Abstract: Purpose This study aims to investigate the comparative importance of factors influencing the customer shift behavior from conventional to Islamic banking for consumer finance in Pakistan. Design/methodology/approach First, a comprehensive analysis of the existing literature was conducted to identify a broad range of factors related to customer shift behavior. Through an expert sampling, 14 essential factors were chosen for further investigation. Second, a questionnaire was developed using the analytical hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(237 reference statements)
0
1
0
Order By: Relevance
“…Customers expect their bank to treat them with courtesy and address their queries in a professional and timely manner, which could stimulate their future trust in their bank (Gokmenoglu and Amir, 2021). In addition, Ahmad et al (2024) have confirmed that bankrelated charges impact customers' perceptions of service experiences, which could guide their future willingness to be associated with their bank in multiple banking contexts. As such, it is hypothesised that:…”
Section: The Moderating Role Of Bank Chargesmentioning
confidence: 82%
“…Customers expect their bank to treat them with courtesy and address their queries in a professional and timely manner, which could stimulate their future trust in their bank (Gokmenoglu and Amir, 2021). In addition, Ahmad et al (2024) have confirmed that bankrelated charges impact customers' perceptions of service experiences, which could guide their future willingness to be associated with their bank in multiple banking contexts. As such, it is hypothesised that:…”
Section: The Moderating Role Of Bank Chargesmentioning
confidence: 82%